Effects of high-speed shear homogenization on properties and structure of the chicken myofibrillar protein and low-fat mixed gel. (August 2019) - Zhou, Lei; Feng, Xiao; Yang, Yuling; Chen, Yinji; Wang, Jingyu; Wei, Sumeng; Li, Shanshan
Abstract: Effects of high-speed shear homogenization on the properties of myofibrillar protein (MP) and low-fat mixed gel were studied. The morphological structure, secondary structure, surface hydrophobicity, sulfhydryl groups and zeta potential of mixed gels were also measured. Under our experimental conditions, 14, 500 rpm was the optimum speed to facilitate the gel strength, water holding capacity and G' values of mixed gel. The fat particles evenly distributed in mixed gel and MP molecules formed a uniform network structure were the important reasons for shear homogenization treatment enhancing the properties of mixed gel. More β-sheet structure content was the underlying cause of shearing treatment to enhanced the mixed gel properties. The changes of zeta potential indicated that MP molecules were difficult to form gel by excessive shear homogenization treatment (higher than 14, 500 rpm). Therefore, 14, 500 rpm was the optimum shear homogenization speed to modify the structure properties, so as to achieve better gel properties of MP-fat mixed gel. Highlights: Low-fat protein gels are desired for food quality and processing. High-speed shear homogenization allows fat particles evenly dispersed in protein gel. High-speed shear homogenization can change the protein gel network structure. Shear homogenization modified the structures to improve the mixed gel properties. Optimized high-speed homogenization realizes improved low-fat protein gel properties.